Pemberdayaan Masyarakat Dalam Peningkatan Kepatuhan Pembayaran Pajak Bumi Dan Bangunan (PBB): Pengabdian - Aulia Indy, Listia; Septiana Putri, Ayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Program aims to increase the level of community compliance in paying Land and Building Tax (PBB), increase public understanding of the obligations and benefits of PBB payments, and reduce PBB payment arrears in the community. This community service was carried out at the Pak Wawi Tempe Factory MSME on Monday, October 20, 2025. Respondents in this service were employees and the community around the Pak Wawi Tempe Factory MSME. The results of the service show that the Community Service Activity (PKM) which focuses on Community Empowerment in Increasing Compliance with Land and Building Tax (PBB) Payments has had a positive impact on increasing knowledge, awareness, and participation of citizens in fulfilling their tax obligations. Through socialization activities, administrative assistance, and tax literacy training, the community has become more aware of the functions and benefits of PBB for regional development. Overall, this PKM activity shows that community empowerment through education, information transparency, and local capacity building is an effective strategy in increasing the level of compliance with PBB payments. It is hoped that similar activities can be continued and expanded to other regions to support the optimization of regional income and more equitable development.